TOM L. BEAÚCHAMP, LAURENCE B. Mc CULLOUGH. Etica Médica, las Responsabilidades Morales de los Médicos, Editorial Labor, S.A.. Barcelona, 1987. - Palafox Bogdanovitch, J. Aurelio (Cuadernos de Trabajo Social, 1988)
Sin resumen